TRIBOLOGICAL STUDIES OF CARBON-ALLOYED TRANSITION METAL DICHALCOGENIDE COATINGS SLIDING AGAINST ALUMINUM AT ELEVATED TEMPERATURES - Sunny, Saniat Jahan (2022)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia